1999
DOI: 10.1099/13500872-145-6-1317
|View full text |Cite
|
Sign up to set email alerts
|

Colony morphotypes on Congo red agar segregate along species and drug susceptibility lines in the Mycobacterium avium-intracellulare complex

Abstract: Isolates of the Mycobacterium avium-intracellulare complex (MAC) have long been known to segregate into transparent, opaque and rough colony morphotypes that differ from each other in clinically important parameters including drug susceptibility and virulence. Here the authors report additional morphotypic variation that occurs on two levels: interspecific (between M. avium and M. intracellulare) and intraspecific (within individual M. avium isolates). Clinical isolates of M. avium grown on Congo red (CR) plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…They are smooth opaque, smooth transparent, and rough. 34 Smooth variants have a dome-shaped appearance, whereas rough variants are characterized by flat, transparent colonies with irregular edges. M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They are smooth opaque, smooth transparent, and rough. 34 Smooth variants have a dome-shaped appearance, whereas rough variants are characterized by flat, transparent colonies with irregular edges. M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Transparent variants predominate in fresh clinical isolates, whereas opaque variants appear with repeated passage in vitro. 34 Conversion to the rough phenotype is irreversible and involves a chromosomal deletion. 34 This change has been observed in M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary studies are under way to compare the hydrophobicity of "M. canettii" and M. tuberculosis. For cultures grown on solid media in the presence of Congo Red [93], the smooth colonies of M. kansasii and "M. canettii" resisted staining by the dye, but two different rough strains of M. tuberculosis absorbed so much dye that they almost merged into the background (Figure 12). In preliminary standard partitioning experiments between hexadecane and water [94], it was found that M. tuberculosis was approximately one fifth more hydrophobic than "M. canettii" (details not shown).…”
Section: Evolutionary and Pathogenicity Aspects Of Cell Envelope Compmentioning
confidence: 99%